Analisis Faktor Yang Mempengaruhi Kepuasan Mahasiswa STIE Sampit - Muamar Muamar; Achmad Syamsudin; Yunikewaty Yunikewaty; Yetrie Ludang; Firlianty Firlianty; Suharno Suharno (FKIP, Universitas Palangka Raya, 2022)
Efforts to improve the quality of human resources, information technology and organizational culture in a campus must be carried out in order to achieve the satisfaction expected by students. High satisfaction for students is expected to generate enthusiasm and will produce good achievements which in the end will become quality graduates. Related to this, there is an inconsistency in previous research on the results obtained, to fill these gaps, the authors are interested in including change management variables. The purpose of this study is to analyze the Quality of Human Resources, Information Technology, Organizational Culture, Change Management and Student Satisfaction. The collection technique begins with making relationships between variables, designing questionnaires and distributing them to proceed with data processing using SmartPLS followed by reading the results of the estimated relationships between variables. This type of research is quantitative research using non-probability sampling technique. The results of this study directly indicate that the quality of human resources, information technology and organizational culture have a positive and significant effect on change management. The quality of human resources, and organizational culture have a positive and significant effect on student satisfaction at STIE Sampit, Information Technology has a positive but not significant effect on student satisfaction. Change Management has a positive and significant impact on STIE Sampit Student Satisfaction, and indirectly the Quality of Human Resources, Information Technology and Organizational Culture has a positive and significant impact on STIE Sampit student satisfaction through Change Management